Developing a Strategy for Interventional Molecular Imaging of Oxidized Low-Density Lipoprotein in Atherosclerosis - Samata S. Pandey MSc; Dorian O. Haskard DM, FRCP, FMedSci; Ramzi Y. Khamis MB, ChB, PhD, MRCP (Molecular Imaging)
The identification of vulnerable coronary artery atherosclerotic plaques offers the prospect of either localized or systematic therapeutic targeting in order to prevent myocardial infarction. Molecular imaging of atherosclerosis adds to morphological imaging by focusing on the immunobiology hidden in and behind the endothelium and therefore may be able to improve the identification of prospective culprit lesions. Our focus has been on identifying arterial accumulation of oxidized low-density lipoprotein (oxLDL) by exploiting advances in knowledge of vascular pathobiology. Here, we reflect on our work developing near-infrared fluorescence imaging of oxLDL using LO1, a monoclonal autoantibody generated in our laboratory. We detail progress to date and discuss our vision on taking the work through the early translational pipeline toward a multitargeted approach in imaging rupture-prone atherosclerotic plaques. Ultimately, molecular imaging of coronary arteries should be able to assess the regional risk that is specific to a lesion, which can then be used in concert with global risk factors to personalize the therapeutic strategy for patients in a way that goes beyond generalized population-based therapies.